Implementasi Pembelajaran Pendidikan Agama Islam dalam Pembentukan Akhlak Siswa SMA A. Wahid Hasyim 4 Gudo Jombang Tahun Pelajaran 2023/2024 - Eny Fatimatuszuhro Pahlawati; Moh. Irfan; Mochamad Syaifuddin (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2024)
This study examines the Implementation of Islamic Religious Education Learning at SMA A. Wahid Hasyim 4 Gudo Jombang in the 2023/2024 Academic Year. This type of research is qualitative research with a descriptive approach. The data collection technique is through interviews, observations and documentation, then analyzed by means of data reduction, data presentation and drawing conclusions. The results of this study indicate that the Implementation of Islamic Religious Education carried out at SMA A. Wahid Hasyim 4 Gudo Jombang is in accordance with the learning steps. The Islamic Religious Education learning process uses the lecture method, telling exemplary stories that can be taken from positive values ​​and using the question and answer method. Supporting factors are teachers, parents, the environment, information media and the existence of time discipline, student interest and facilities and infrastructure. While the inhibiting factors are limited time, lack of awareness in students, lack of ability to utilize cellphones for positive things, their environmental factors, lack of religious education in the family and parental attention and also lack of facilities and infrastructure. Keywords : Learning; Islamic Religious Study; Student’s Morals